SEM Analysis of MTAD Efficacy for Smear Layer Removal from Periodontally Affected Root Surfaces - B. Houshmand; M. Ghandi; MH. Nekoofar; Gh. A.Gholamii; R. K. Tabor; P. M. H. Dummer (Tehran University of Medical Sciences, 2011)
Objective: Biopure® MTAD (Dentsply Tulsa Dental, USA) has been developed as a final irrigant following root canal shaping to remove intracanal smear layer. Many of the unique properties of MTAD potentially transfer to the conditioning process of tooth roots during periodontal therapy. The aim of this ex vivo study was to evaluate the effect of MTAD on the removal of smear layer from root surfaces. Materials and Methods: Thirty two longitudinally sectioned specimens from 16 freshly extracted teeth diagnosed with advanced periodontal disease were divided into four groups. In group 1 and 2, the root surfaces were scaled using Gracey curettes. In group 3 and 4, 0.5 mm of the root surface was removed using a fissure bur. The specimens in group 1 and 3 were then irrigated by normal saline. The specimens in groups 2 and 4 were irrigated with Biopure MTAD. All specimens were prepared for SEM and scored according to the presence of smear layer. Results: MTAD significantly increased (P=0.001) the smear layer removal in both groups 2 and 4 compared to the associated control groups, in which only saline was used. Conclusion: MTAD increased the removal of the smear layer from periodontally affected root surfaces. Use of MTAD as a periodontal conditioner may be suggested.